Effect of climate change on rice (oryza sativa) production in Malaysia / Muhammad Hazwan Hasnol Habibie Hayat - Hayat, Muhammad Hazwan Hasnol Habibie (2022)
Malaysia's self-sufficiency programme has been centred on rice cultivation, the country's principal staple food and food crop. Rice also contributes significantly to employment and economic growth, particularly in developing nations. In a tropical climate, sunshine and rainfall are two critical meteorological factors, and fluctuations in either have a major impact on crops and yields over the seasons. For Malaysia, the effects of climate change are wreaking havoc on the agricultural sector, particularly rice, the country's primary grain. This conclusion is consistent with the findings of other research, which indicated that the effects of climate change will have a considerable influence on Malaysia's rice output.